Inhabiting the peripheries: a Bourdieusian exploration of international students’ encounters in Kyrgyzstan - Eusafzai, Hamid Ali Khan (Frontiers in Education, 2023)
This research employs a qualitative lens to explore the multifarious hurdles international students face in underrepresented educational destinations, taking Kyrgyzstan as an exemplar. Leveraging Bourdieu's theoretical insights, the study unearths nuanced personal, social, and academic adversities. Central to the study's findings are the prevailing power imbalances, positioning international students at a disadvantage due to varying habitus and insufficient cultural capital. Notwithstanding these issues, these students exhibit determination and agency. The research underscores the urgency for more inclusive practices, curbing discrimination, rebalancing power structures, and fortifying student support mechanisms, providing policy directions for enhanced international student experiences in analogous settings.